Molecular cloning, characterization and expression of a jasmonate biosynthetic pathway gene encoding allene oxide cyclase from Camptotheca acuminata. Issue 6 (13th November 2008) - Pi, Yan; Liao, Zhihua; Jiang, Keji; Huang, Beibei; Deng, Zhongxiang; Zhao, Dongli; Zeng, Hainian; Sun, Xiaofen; Tang, Kexuan
Abstract : AOC (allene oxide cyclase; EC 5.3.99.6), an essential enzyme in jasmonic acid and its methyl ester biosynthesis, was cloned from Camptotheca acuminata (named as CaAOC ), a native medicinal plant species in China. CaAOC had significant similarity at the amino-acid level with AOCs from other plant species. Comparison between the sequences of the full-length cDNA and genomic DNA of CaAOC revealed that the genomic DNA of CaAOC contained an 89-bp intron and a 240-bp intron. Southern-blot analysis indicated that CaAOC was a multiple-copy gene, and real-time quantitative PCR analysis showed that CaAOC was expressed constitutively in all organs tested, with the highest expression level in leaves. The results from treatment experiments using different signalling components, including methyl jasmonate, abscisic acid, salicylic acid and H2 O2, revealed that expression of CaAOC had a prominent diversity. Heavy metal (copper) significantly enhanced CaAOC expression, whereas wounding (induced by UV-B) was not so effective.